The impact of leadership values and culture on sustainable development strategies - Ratau, Neo (Graduate School of Business (GSB), 2024)
With the right management tools and access to best practices, South African companies can create and capture significant value for multiple stakeholders. This can be achieved by innovating business models with built-in sustainability. Sustainability business models can help alleviate the country's top three socioeconomic pain points (inequality, unemployment, and poverty), whilst adding significant economic value. Human beings' decisions are a function of an internal value system. Accordingly, executive leadership decisions do not only stem from external pressures and drivers, but also from an internal value system. The question this research sought to answer was what the external and internal drivers of business model innovation for sustainability are, to help determine the motive behind executives' choice to integrate sustainability into business models. Motive often determines longevity of a strategy. Aiming to answer this research question, qualitative research methodology was carried out utilising a single case study method on Discovery, a prominent South African health insurance company. This exploration sought to establish an understanding of the thinking process and lived experience of the founding leadership in responding to external and internal drivers of their business model. Fourteen respondents were interviewed using one-on-one interviews. The respondents were comprised of eight Discovery Group executives, three industry experts from the regulatory side, and three equity analysts. The themes that were found as drivers for Discovery's business model were leadership capability, regulation, legitimacy, as well as the pursuit of competitive advantage amongst industry peers. Discovery's leadership highlighted internal purpose as the main rationale for their shared value business model. This study contributes to knowledge by providing a framework for companies to utilise, with an aim to reduce their implementation risk, when designing business model innovation for sustainability. In so doing, it adds to the growing body of sustainable business model knowledge in South Africa.